Assessment of Surface Glycan Diversity on Extracellular Vesicles by Lectin Microarray and Glycoengineering Strategies for Drug Delivery Applications. Issue 2 (1st December 2021) - Shimoda, Asako; Miura, Risako; Tateno, Hiroaki; Seo, Naohiro; Shiku, Hiroshi; Sawada, Shin‐ichi; Sasaki, Yoshihiro; Akiyoshi, Kazunari
Abstract: Extracellular vesicles (EVs) are released by all types of mammalian cells for cell–cell communication. In this study, surface glycans on EVs are compared in terms of their cell type, size, and isolation method to examine whether EV glycan profiles by lectin microarray can be used to define EV subpopulations. Moreover, EVs are glycoengineered with four distinctive surface glycan patterns and evaluated their cellular uptake efficiencies for potential drug delivery applications. Both similarities and differences in glycan patterns are identified on EVs obtained under each experimental condition. EV size‐ and isolation method‐dependent lectin‐binding patterns are observed. Moreover, cellular uptake behaviors of EVs are affected by EV glycan profiles and acceptor cells. The in vivo biodistribution of EVs is also dependent on their glycan profile. These results suggest that EV surface glycans are a potential novel indicator of EV heterogeneity, and glycoengineering is a useful approach to regulate cell–EV interactions for biomedical applications. Abstract : An evanescent field fluorescence‐assisted lectin microarray makes it possible to comprehensively determine glycan patterns on intact extracellular vesicles (EVs). EV surface glycans can be used as indicators of EV heterogeneity, and glycoengineering is a helpful technique for manipulating EV‐to‐cell interactions.